ON THE COMMON ORIGIN OF SOUTHEAST ASIA OF PHYTOPLASMA ASSOCIATED DISEASES OF COCONUT - Hugh C Harries (International Coconut Community, 1998)
The association of phytoplasma with two wilt diseases of coconut in Indonesia might be seen as a threat to the Asian and Pacific regions because epidemic phytoplasma diseases of coconut in America and Africa arc spreading out of control. Yet research has already suggested that these diseases originated in the Far East where resist varieties can bc found. Recently, a workshop was held to assess lethal diseases of coconuts caused by phytoplasmas and their importance in southeast Asia. The workshop took place in Manado, North Sulawesi , Indonesia on 16‑17 February 1998 and the full proceedings will be published separately. The participants beard about the situation of coconut development and the unpact of etiology of coconut wilt diseases in Indonesia. As 95% of coconuts in Indonesia are grown by small farmers the workshop was also informed of the impact of coconut diseases on small farmers. Specific reports were made on the history and status of Natuna wilt disease and the distribution of epiderniology of Kahmantan wilt diseasc. These have both been associated writh phytoplasma. Other reports were made on the development of coconut wilt discase in Kotawaringin, Timur District, Central Kalimantan Province and on the history and status of yellow disease of coconut palm in Central Sulawesi, for which no causal agents have yet been identified. Intemational representatives also spoke about root (wilt) and Tatipakka diseases of coconut in India and declffie diseases of coconut in Sri Lanka that have not been associated with phytoplasma and on lethal diseases in America and Africa that arc associated with phytoplasma. The history and biology of phytoplasmas as plant pathogens and diagnostic methods for coconut diseases; were explained in a session on the pathogen. Safe germplasm movernent for scientific purposes of conservation and exchange was dealt with and, for fanners and extension agents, the practical application of resistant local coconut varieties for replanting was advised.